A bleeding rectosigmoid mass in a 41-year-old woman - Giuseppe Grande; Zulli Claudio; Mariano Sica; Angelo Caruso; Raffaele Manta; Vincenzo Mirante; Helga Bertani; Rita Luisa Conigliaro (Turkish Journal of Gastroenterology, 2019)
-